2015
DOI: 10.1002/ajmg.a.37343
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent synonymous KAT6B mutation causes Say‐Barber‐Biesecker/Young‐Simpson syndrome by inducing aberrant splicing

Abstract: Mutations of the histone acetyltransferase-encoding KAT6B gene cause the Say-Barber-Biesecker/Young-Simpson (SBBYS) type of blepharophimosis-"mental retardation" syndromes and the more severe genitopatellar syndrome. The SBBYS syndrome-causing mutations are clustered in the large exon 18 of KAT6B and almost exclusively lead to predicted protein truncation. An atypical KAT6B mutation, a de novo synonymous variant located in exon 16 (c.3147G>A, p.(Pro1049Pro)) was previously identified in three unrelated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…From the few exceptions, one is a recurring synonymous p.Pro1049Pro with a de novo origin that was found to cause partial loss of exon 16 at the RNA level because of a newly created splice acceptor site within this exon with a resulting 127 bp out‐of‐frame deletion leading to a frameshift and subsequent premature stop codon. This reclassified a synonymous variant for a truncating one with a correct description of p.Ala1008Arg fs *62 . In contrast, missense variant p.Trp987Arg was found in only one SBBYSS patient whose parents were not tested, and this variant's possible pathogenic potential was hypothesized via in silico prediction of conservation of the site and its absence in dbSNP .…”
mentioning
confidence: 99%
“…From the few exceptions, one is a recurring synonymous p.Pro1049Pro with a de novo origin that was found to cause partial loss of exon 16 at the RNA level because of a newly created splice acceptor site within this exon with a resulting 127 bp out‐of‐frame deletion leading to a frameshift and subsequent premature stop codon. This reclassified a synonymous variant for a truncating one with a correct description of p.Ala1008Arg fs *62 . In contrast, missense variant p.Trp987Arg was found in only one SBBYSS patient whose parents were not tested, and this variant's possible pathogenic potential was hypothesized via in silico prediction of conservation of the site and its absence in dbSNP .…”
mentioning
confidence: 99%
“…Until now, 45 SBBYSS, 15 GPS patients, and 5 additional patients with combined phenotypes between the two syndromes have been reported with KAT6B mutation [ 2 3 5 6 7 8 ]. Of those 65 KAT6B mutations, 53 mutations were located in exon 18.…”
Section: Discussionmentioning
confidence: 99%
“…While GPS mutations were located more proximally in the same exon, losing both domains led to gain-of-function mutation. However recent studies identified mutations more proximal in exon 15, 16, 17 with the typical features of SBBYSS [ 7 8 ]. The mutation occurred in exon 11 in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid abnormalities are often observed in patients with KAT6B -related disorders 10 . However, the severity and onset of the phenotype seem to be variable 1115 . Indeed, the present patient had normal TSH levels at the time of neonatal mass screening.…”
mentioning
confidence: 99%